TODAY'S CITIES: CHALLENGES FOR REHABILITATION NURSES FOR INCLUSION - Ana Isabel Ribeiro Da Silva Pereira; Maria Manuela Ferreira Pereira Da Silva Martins; Rute Salomé da Silva Pereira; Bárbara Pereira Gomes; João Santos; Paulo Alexandre Matos Cunha (Associação Portuguesa dos Enfermeiros de Reabilitação, 2020)
The architectural barriers on public highway cause inaccessibility, contributing to the limitation of functionality and creation of disability. Objectives: to analyze the conditions of accessibility on public highways in view of the needs of disabled people; To understand how external environments contribute to the social inclusion of people with disabilities; Methodology: Quantitative, observational, descriptive, cross-sectional study from a non-probabilistic sample by rational choice - 31 streets (62 pedestrian paths), using an ad hoc evaluation grid (Decree-Law 163/2006) (1). Results: 75.8% of the pedestrian paths evaluated allow access and permanence of a person in a wheelchair, as well as the frontal and lateral reach to objects placed on the road, however 22.6% of the paths are not accessible. Conclusion: although the current legislation and accessibility policies, there are still architectural barriers on public highways that rehabilitation nurse directly influence the independence of disabled people, which suggests that should develop effective work with municipalities.